2023
DOI: 10.1021/acsami.3c09257
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Effects of Atomic Vacancy Defects on Friction

Lina Zhang,
Weibin Chen,
Xinfeng Tan
et al.

Abstract: The presence of defects such as vacancies has a significant impact on the frictional properties of 2D materials that are excellent solid lubricants. In this study, we demonstrate that the nonmonotonic effect of Te vacancy defects on the friction of MoTe2 is related to the change in the maximum sliding energy barrier due to the variation in tip position. The experimental results of atomic force microscopy suggest that the friction shows an overall increasing trend with the increase in Te vacancy density, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The degree of vacancy defect effect on friction enhancement follows: V Mo < V S < V S2 < V MoS3 < V MoS6 . Zhang et al [107] performed MD simulations to investigate the increase in friction force with Te vacancy defect in MoTe 2 and attribute it to the large and more sliding energy barriers that the tip overcome as shown in figures 8(g) and (h). Their simulations found that the nonmonotonic variation of friction with defect density is due to that the variation of tip in-plane position perpendicular to the sliding direction during the sliding process, which changes of the maximum sliding potential barrier as shown in figure 8(i).…”
Section: Defectmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of vacancy defect effect on friction enhancement follows: V Mo < V S < V S2 < V MoS3 < V MoS6 . Zhang et al [107] performed MD simulations to investigate the increase in friction force with Te vacancy defect in MoTe 2 and attribute it to the large and more sliding energy barriers that the tip overcome as shown in figures 8(g) and (h). Their simulations found that the nonmonotonic variation of friction with defect density is due to that the variation of tip in-plane position perpendicular to the sliding direction during the sliding process, which changes of the maximum sliding potential barrier as shown in figure 8(i).…”
Section: Defectmentioning
confidence: 99%
“…force field and electronic field, is an effective avenue to manipulate the frictional properties of 2D materials, and intensive atomistic simulations have addressed on this topic. Sun et al [109] found that the interlayer sliding friction of a graphene/graphene interface can decrease Reprinted with permission from [107]. Copyright (2023) American Chemical Society.…”
Section: External Fieldmentioning
confidence: 99%
See 1 more Smart Citation